Steroid‐Based Amphiphiles for Membrane Protein Study: The Importance of Alkyl Spacers for Protein Stability. (29th May 2018) - Ehsan, Muhammad; Das, Manabendra; Stern, Valerie; Du, Yang; Mortensen, Jonas S.; Hariharan, Parameswaran; Byrne, Bernadette; Loland, Claus J.; Kobilka, Brian K.; Guan, Lan; Chae, Pil Seok
Abstract: Membrane proteins allow effective communication between cells and organelles and their external environments. Maintaining membrane protein stability in a non‐native environment is the major bottleneck to their structural study. Detergents are widely used to extract membrane proteins from the membrane and to keep the extracted protein in a stable state for downstream characterisation. In this study, three sets of steroid‐based amphiphiles—glyco‐diosgenin analogues (GDNs) and steroid‐based pentasaccharides either lacking a linker (SPSs) or containing a linker (SPS‐Ls)—have been developed as new chemical tools for membrane protein research. These detergents were tested with three membrane proteins in order to characterise their ability to extract membrane proteins from the membrane and to stabilise membrane proteins long‐term. Some of the detergents, particularly the SPS‐Ls, displayed favourable behaviour with the tested membrane proteins. This result indicates the potential utility of these detergents as chemical tools for membrane protein structural study and a critical role of the simple alkyl spacer in determining detergent efficacy. Abstract : Gentler detergents : New steroid amphiphiles with a pentasaccharide head group displayed favourable behaviour for membrane protein stability. This study indicates the important role of a flexible alkyl spacer in determining detergent efficacy for protein stabilisation.